MODELING OF THE “Y” AND “G” CODE TRANSMISSION PROCESS OF THE MICROELECTRONIC CODE TRANSMITTER USING PETRI NETS (American Journal of Interdisciplinary Research and Development, 2022)
Currently, microprocessor, microelectronic systems and devices used in railway automation and remote control systems are widely used. The use of systems and devices for railway automation and remote control, developed on the basis of microelectronics and microprocessor elements, provides an increase in the level of reliability compared to systems based on electromagnetic relays.